A MSN-based tumor-targeted nanoplatform to interfere with lactate metabolism to induce tumor cell acidosis for tumor suppression and anti-metastasis. Issue 5 (23rd January 2020) - Chen, Zhao-Xia; Liu, Miao-Deng; Guo, Deng-Ke; Zou, Mei-Zhen; Wang, Shi-Bo; Cheng, Han; Zhong, Zhenlin; Zhang, Xian-Zheng
Abstract : A tumor targeting drug delivery system was designed to interfere with lactate metabolism for tumor therapy and anti-metastasis research. Abstract : Lactate, the main contributor to the acidic tumor microenvironment, not only promotes the proliferation of tumor cells, but also closely relates to tumor invasion and metastasis. Here, a tumor targeting nanoplatform, designated as Me&Flu@MSN@MnO2 -FA, was fabricated for effective tumor suppression and anti-metastasis by interfering with lactate metabolism of tumor cells. Metformin (Me) and fluvastatin sodium (Flu) were incorporated into MnO2 -coated mesoporous silicon nanoparticles (MSNs), the synergism between Me and Flu can modulate the pyruvate metabolic pathway to produce more lactate, and concurrently inhibit lactate efflux to induce intracellular acidosis to kill tumor cells. As a result of the restricted lactate efflux, the extracellular lactate concentration is reduced, and the ability of the tumor cells to migrate is also weakened. This ingenious strategy based on Me&Flu@MSN@MnO2 -FA showed an obvious inhibitory effect on tumor growth and resistance to metastasis.